improve the therminal performance of air flat- plate solar collector by using phase change materials - ابراهيم, نور; رامي جورج (Latakia University Journal -Engineering Sciences Series, 2023)
The research aims to study the possibility of experimentally improving the thermal performance of the air flat- plate solar collector by adding a phase change material and comparing it with the performance of a conventional air flat- plate solar collector under the same climatic conditions in the city of Safita for the year 2021-2022. The experimental results showed that the use of the phase change material (paraffin wax) in the air collector to an improvement the thermal performance of the collector and thus increased the amount of useful heat dissipated, which increases with the increase in the amount of paraffin wax, where the percentage of increase in the amount of heat dissipated was 62.5% when using 4.5 [ Kg] of paraffin wax, and when using 3 [kg] of paraffin wax, the rate of increase in the amount of heat was 26.8%, while it recorded 18.4% when supplying the collector with 1.5 [kg] of paraffin wax, In addition The use of the phase change material increased the working hours of the air collector compared to the conventional one. As for changing the flow and its effect on the performance of the air collector, the results showed that reducing the flow of one of the collectors by half leads to an increase in the temperature of the air exiting the collector compared to the temperature of the air exiting the other collector at the reference flow, noting that both collectors are equipped with 1.5 [kg] of paraffin wax, where the rate of increase in temperature was 10.4% .